Codon-optimization in gene therapy: promises, prospects and challenges - Paremskaia, Anastasiia Iu; Kogan, Anna A.; Murashkina, Anastasiia; Naumova, Daria A.; Satish, Anakha; Abramov, Ivan S.; Feoktistova, Sofya G.; Mityaeva, Olga N.; Deviatkin, Andrei A.; Volchkov, Pavel Yu (Frontiers in Bioengineering and Biotechnology, 2024)
Codon optimization has evolved to enhance protein expression efficiency by exploiting the genetic code's redundancy, allowing for multiple codon options for a single amino acid. Initially observed in E. coli, optimal codon usage correlates with high gene expression, which has propelled applications expanding from basic research to biopharmaceuticals and vaccine development. The method is especially valuable for adjusting immune responses in gene therapies and has potential in creating tissue-specific therapies. However, challenges persist, such as the risk of unintended effects on protein function and the complexity of evaluating optimization effectiveness. Despite these issues, codon optimization is crucial in advancing gene therapeutics. This review provides a comprehensive review of the current metrics for codon-optimization, its practical usage in research and clinical applications, in the context of gene therapy.